Ações afirmativas, educação e relações raciais: conservação, atualização ou reinvenção do Brasil? - Rodrigo Ednilson de Jesus (2011)
This research, which has a bibliographical and qualitative characteristic, has two distinct but related aims, what explains the thesis division in two parts. The main aim in the first part is to discuss the central role that basic and higher education has played in the constructive process of Brazilian society up to the present time, sometimes keeping socialinequalities and sometimes making social inclusion possible and promoting social, economic and cultural emancipation of the poorest. The second part of this work aims to discuss how current proposals of Affirmative Actions, which have helped to take up again discussions onracial relations in Brazil, have provoked the State, universities and civil society to re-evaluate the ground of the modern Brazilian State, principally after the Proclamation of the Republic in 1889. The thesis I will support is that public policies presenting racial features that have been carried out in Brazil, especially Affirmative Actions policies, often reduced to Quota policies, broke down the historical image of Brazil, always legitimated by Brazilian society, which reflects the Brazilian people and their sui generis racial relations. Theoretical and political commitments regarding Quota policies and Affirmative Actions, especially the positioning of16 expositors who participated in the Hearing on Affirmative Actions policies to reserve places in Higher Education carried out by the Federal Supreme Court in March of 2010, were used in order to understand divergent social representations on race and racism, equality andinequality, justice and injustice, national identity and the formal education role. The analysis of the speeches on the constitutionality or the unconstitutionality of race Quota in universities and colleges, the theme of the Hearing, evidenced that we are not coping with metaphors, but also with material and symbolic disputes to impose conceptions aboutBrazil and to appropriate a different proportion of the available resources - material and symbolic. It has also evidenced that the divergent representations of Brazil and of Brazilian race relations can vary from those that denounce the race discrimination in many socialcontexts to those that sustain the unity of race relations. These two points of view are closely associated with how the social actors think about the political alternatives as more adequate and coherent in relation to the nation projects they are inserted. To whom that denounce thepolicy on race as unconstitutional the policy on Quota and Affirmative Actions might not be the most appropriate alternative policies to provide the preservation of Rainbow Nation, in reference to Brazilian racial plurality. On the other hand, to whom the race policies areconstitutional, just with the explanation about the modern ground on which Brazilian inequalities are founded it would be possible to conceive of other possible policies more adequate to reinvent the country. It would enable the emergence of a new social reality able to combine the racial equality as an ideal and the respect for differences.